REPRESENTASI NILAI FEMINIS TOKOH AMBA DALAM NOVEL AMBA KARYA LAKSMI PAMUNTJAK (Sebuah Analisis Wacana Sara Mills dan Nilai Pendidikan Karakter) - Cahyo Hasanudin (Universitas PGRI Adi Buana Surabaya, 2015)
Abtract Amba Novel waspublished on September 2012. AppearingAmbanovel had positive comments of art beneficiary. In height society appreciation to Amba novel making the novel included national best seller novel rating. This research had purposes (1) How to asses Amba's figure feminist in Amba novelby Laksmi Pamuntjak? (2) How to introduce Amba novel byLaksmi Pamuntjakas feminist discourse?(3) What kind of education’s characters points that consist onAmba novelby Laksmi Pamuntjak?This research used deskriptive approach in qualitative research. Reality sources of discourse analized based on corpus data on Amba Novel by Laksmi Pamuntjak which focus on feminist discourse analized was developed by Sara Mills. Result of this research showed (1) feminist values of Amba’sfigure on Amba novel by laksmi pamuntjak can be seen by ambas’s characters who smart and forward thinking, both of value was represented by laksmi pamuntjak through Amba’s figure so that women had right similarity. Feminist value could by catecorized as liberal feminist. (2) Amba novel by laksmi pamuntjak is made as feminist discourse through Sara Mills discourse analysis consept, it could by seen by gender representation which descirbet on Amba novel. (3) most of education character values were found on Amba novel, religious, discipline, creative, and social caring. Key Word: Amba novel, Feminist Discourse analysis, Character education.